History Education in the Age of Disinformation: The Role of Historical Literacy in Social Studies Learning - Dewa Made Alit; Agus Mursidi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
The rapid growth of digital media has led to a surge in disinformation, significantly affecting students’ understanding of history and weakening critical civic engagement. This article aims to examine the role of historical literacy in countering disinformation within social studies education, particularly in Indonesian secondary schools. Using a qualitative-descriptive approach, this study employs literature review and document analysis of curriculum guidelines, history textbooks, and teaching modules. Thematic content analysis was applied to explore how historical literacy can be integrated into history instruction and how it supports critical thinking, source evaluation, and civic awareness. The findings highlight three key challenges in history education during the disinformation era: low student interest in history, the prevalence of biased or distorted historical content, and students' limited ability to verify sources. The study reveals that strategies such as inquiry-based learning (IBL), multiperspective analysis, digital resource integration, and document-based instruction (DBI) significantly enhance students' historical literacy. These strategies foster deeper engagement with historical content and strengthen students’ critical thinking and verification skills. Furthermore, the study presents several best practices from schools that successfully implemented historical literacy approaches, indicating positive impacts on students' ability to analyze historical narratives and resist misinformation. The novelty of this research lies in its integrative perspective—linking historical literacy, digital citizenship, and civic engagement in social studies. It positions historical literacy not merely as a cognitive skill but as a vital competency for navigating a digital, post-truth society. The article recommends developing teacher training programs and curriculum materials that emphasize historical thinking, source critique, and digital literacy. Strengthening historical literacy in social studies will equip students to become informed, reflective, and responsible citizens in the age of disinformation.